Zoster-like primary Herpes Simplex Virus infection in a 6-year-old baby-girl. - Rana, P.; Garofalo, L.; Bonifazi, E. (European Journal of Pediatric Dermatology, 2007)
Zoster-like primary Herpes Simplex Virus infection in a 6-year-old baby-girl. Here is reported a case of zoster-like primary infection with Herpes Simplex Virus (HSV) in a 6-month-old baby girl, wich was mediated by the saliva of her father affected by recurrent labial HSV infection. Its zoster-like distribution seems due to the spreading of HSV from the ganglion to the skin through the Schwann cells of the nervous sheat.